2022
DOI: 10.13189/saj.2022.100523
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Learning Space as an Alternative for Physical Education Learning Post Covid-19 Pandemic

Abstract: The Covid-19 pandemic has resulted in educational disruptions in around 80% of children worldwide and has had a devastating impact on the effectiveness of physical education (PE) learning. This research aims to design a hybrid learning space (HLS) as an alternative to PE learning post the pandemic. The participants consisted of 72 PE teachers spread across 35 Senior High Schools and covered in 12 sub-districts in Central Lombok Regency, West Nusa Tenggara. This research used a mix of methods with embedded desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 55 publications
(72 reference statements)
0
2
0
Order By: Relevance
“…The primary objective of blended education is to facilitate the development of students into individuals who possess the ability to engage in continuous learning and enhance their competencies and passions [19][20][21]. Multiple investigations have indicated that fulltime online learners exhibit considerably lower rates of school and extracurricular club participation compared to blended learners [22][23][24]. The potential consequences of this phenomenon on the future social behaviors of pupils are likely to be detrimental.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary objective of blended education is to facilitate the development of students into individuals who possess the ability to engage in continuous learning and enhance their competencies and passions [19][20][21]. Multiple investigations have indicated that fulltime online learners exhibit considerably lower rates of school and extracurricular club participation compared to blended learners [22][23][24]. The potential consequences of this phenomenon on the future social behaviors of pupils are likely to be detrimental.…”
Section: Discussionmentioning
confidence: 99%
“…To optimize students' longterm productivity and efficiency, this educational approach prioritizes the provision of opportunities for selfdirected and sustainable learning [19][20][21]. Recent study findings have revealed that students who only participated in online education exhibited notably diminished levels of engagement in extracurricular pursuits and school when compared to their peers who were enrolled in a blended learning approach [22][23][24]. The potential social skills of the child would be negatively impacted as a result.…”
Section: Introductionmentioning
confidence: 99%